Cerdas Antibiotik: Edukasi Penggunaan Antibiotik yang Tepat sebagai Solusi Atasi Resistensi - Agustina Nila Yuliawati; Ni Made Gita Widani; Gizella Aurel; Desak Made Dian Priskila; Kadek Sintya Dewi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Antibiotic resistance is a serious public health issue, primarily caused by the improper use of antibiotics, such as purchasing without a doctor's prescription, stopping treatment prematurely, and a lack of understanding about antibiotic function. This condition also occurs in Buahan Village, Tabanan Regency, Bali, prompting the need for educational intervention. The educational activity was carried out using the Communication, Information, and Education (CIE) approach, involving material delivery, interactive discussions, and evaluation through pre-test and post-test to measure changes in public knowledge and behavior. Data were analyzed using validity, reliability, normality tests, and the Wilcoxon test. The results showed a significant increase in knowledge and a positive change in behavior after the educational session, with Wilcoxon test results showing a significance value of <0.05. The questionnaire used was proven to be valid and reliable. These findings indicate that structured and interactive education is an effective solution to combat antibiotic misuse and prevent resistance at the community level. Therefore, such educational efforts are essential to be implemented consistently to support the control of antibiotic resistance.